Healthy family index assessment through community-based health information system approach - Rico Kurniawan; Ryza Jazid Baharuddin Nur; Sayekti Yuliyanti; Dion Zein Nuridzin; Neng Tine Kartinah (International Journal of Public Health Science (IJPHS), 2021)
The healthy Indonesia program with a family approach (PIS-PK) has not been implemented optimally. There are several obstacles and challenges in this program’s implementation, e.g., human resources. A community-based health information system (CBHIS) is a strategic approach to obtain data and information at the population level by directly involving cadres and the community. A project with the CBHIS approach was implemented in Kasemen Village, Serang, Banten Province, Indonesia to support the PIS-PK program. The study aimed to determine the population’s health status according to the healthy family index through the CBHIS approach. The data of healthy family indicators in the village were collected by cadres using a mHealth application. Overall, 1316 households consisting of 5312 residents were registered. The analysis results of the healthy family index showed that most families in the Kasemen subdistrict were pre-healthy (64.2%), almost one third were unhealthy (27.8%) and only a small proportion were healthy (8%). Assessing the healthy family index through the CBHIS approach can support decision-making at the community level, thereby determining the magnitude of family health problems and providing appropriate interventions to improve community health status. Well-trained cadres equipped with better electronic data collection tools may be an alternative to community-based data collection.